Peran Konselor Dalam Meningkatkan Motivasi Belajar dan Hubungan Sosial Emosional Siswa - Zahara, Nelsi; Hartini; Kholilah Harahap, Emmi (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This study aims to solve the problems that occur in the field regarding learning motivation and social emotional relationships, namely that there are some students who still have difficulty accepting the lesson material. The research method used in this study with a qualitative approach with the subjects in this study being SMP Negeri 3 Rejang Lebong. Data collection techniques using documentation, interviews, observation and documentation. The results of this study indicate that students' learning motivation and social emotional relationships can be categorized as low. This can be seen from students' learning motivation, namely students have difficulty accepting the lesson material given by the teacher, students do not like the teacher's teaching method. While seen from students' social emotional relationships, students often fight for reasons of taking their friends' things, fighting over girlfriends, making noise in class, teasing each other between friends and there are students who play with different friends in other classes.